La tecnica: Strumento di incatenamento o di liberazione? Tra Nietzsche e Prometeo - Adesso, Gemma Bianca (Bollettino Filosofico, 2023)
This paper consists of three parts: in the first one, we point out the problem of technology in Nietzsche’s thought and its contradictory relationship with nature and science; in the third one, we meditate on Prometheus since Nietzsche allows us to interpret the myth as the symbol of the Western knowledge crisis. An intermediate space will be dedicated to the image of chains which, according to Nietzsche, starting from the connotative symbol of Prometheus, become metaphor of education as well as of technology. Keywords: Chains, Nature, Nietzsche, Prometheus, Technology